Perancangan Media Promosi Jasalindo Sport - Sundri Natali; Rakhmad Maulidi; Rina Nurfitri (LPPM STIKI Malang, 2022)
Jasalindo Sport design is a company engaged in rescue and diving, shipwrecking and the provision of diving equipment, the Company does not yet have a promotional media that can be known to the public. Therefore, it is necessary to design a media promotion Jasalindo Sport to improve the image of the company that can be known to the public and increase sales. The method of design using sadjiman Ebdi Sanyoto's method of collecting observation and interview data, with SWOT data analysis (Strengths, Weakness, Opportunities, and Threats (Threats) after that formed a final design that was then tested to the target audience. Jasalindo Sport's promotional media design resulted in a video company Profile and supporting media posters, brochures, catalogs, x-banners, published on youtube, Instagram, Facebook. In conclusion, the resulting media certainly has advantages and disadvantages in helping to introduce Jasalindo Sport.